THE EFFECTIVENESS OF USING SCRAMBLED SENTENCES IN TEACHING WRITING RECOUNT TEXT - M Muklas; Nurbayanah Nurbayanah (Sriwijaya University Learning and Education International Conference, 2018)
The objective of this research was to know whether or not there is significant different between students who are taught by using Sscramble Sentencesand the students who are taught by using Cconventional Technique in teaching writing recount text tothe eighth grade students of SMP Negeri 1 Buay Madang Timur”. This research was quantitative research, using experimental method and true experimental design.Then, the population of the research were 208 studentsfrom six classes. Andthe sample of the study were 72 students, consist of two groups, namely experimental group (VIII.C)consist of 36 students and control group (VIII.D) consist of 36 students which choosen by cluster random sampling. In this research, the researcher used written test as an instrument for the collecting the data. The data obtained from Iindependent t-test analysis by using SPSS 20, between the result of posttest in experimental group and control group. Based on the calculation by using Iindependent t-test in SPSS 20, the writer found that t obtained was higher than t table (4.174 > 1.994) at the significant level α=0.05 in two tailed testing. It meant that there was any significant differences between experimental group and control group. So, the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted.It can be concluded that SscrambleSentences was significantly effective in teaching writing recount texttothe eighth grade students of SMP Negeri 1 Buay Madang Timur.